Optimization of the environmental protection tax system design based on artificial intelligence - Zhang, Jing (Frontiers in Environmental Science, 2023)
Introduction: China achieved significant economic growth in the past two decades, and the sustained economic growth also brings negative implications for the environment. The Chinese government has introduced various fiscal reforms to mitigate the negative implication of the environment in the economy. Modernization of China's governance system and improvement of social development were the main goals of the 14th Five-Year Plan. Methods: Literature combing method and Chart analysis method. Result: Artificial intelligence promotes the efficiency of bonded governance environment and boosts national management modernization. Discussion: This paper suggests that the artificial intelligence construction of the environmental protection tax system improves tax collection and management, tax payment service, and tax management. In addition, the government should adopt other strategies to promote a clean environment, such as tax exemption for green and cleaner production. Easy loans should be provided to the exports, especially those contributing to clean energy production.